Dramaturgy in the making user's guide for theatre practitioners - Trencsényi, Katalin (Bloomsbury, 2015)
A thorough study of contemporary dramaturgical practices which draws on many examples from the work of leading theatre practitioners from the UK, Europe and North America. It maps the various ways in which a dramaturg may work in the theatre-making process and provides a theoretical framework to aid the reader in their own practice.